The Effect of Failure Criteria on Liquefaction and Pore Pressure Prediction in Non-Plastic Soils - Carmine P. Polito (Geotechnics, 2025)
Since the 1960s, cyclic triaxial tests have been utilized to assess the liquefaction susceptibility of cohesionless soils. While standardized procedures exist for conducting cyclic triaxial tests, there remains no universally accepted criterion for defining liquefaction in a laboratory test. The selection of a liquefaction criterion significantly impacts the interpretation of the test results and subsequent analyses. To quantify these effects, more than 250 cyclic triaxial tests were evaluated using both stress-based and strain-based liquefaction criteria. The analyses performed focused on two aspects of the liquefaction behavior: the number of cycles of loading required to initiate liquefaction and the amount of normalized dissipated energy per unit volume that must be absorbed into the specimen in order for it to liquefy. The findings indicate that for soils susceptible to flow liquefaction failures, the number of loading cycles required to induce liquefaction decreases. They also show that the amount of energy dissipation required to trigger liquefaction remains largely consistent across different failure criteria. However, for soils prone to cyclic mobility failures, both the number of loading cycles and the amount of dissipated energy required to cause liquefaction were found to vary significantly depending on the failure criterion applied.